Association between three-territory sign and prognosis of acute ischemic stroke patients with malignancy - Cheng, Yuying; Ning, Yuye; Zhao, Yixin; Cao, Xiangqi; Liu, Hui; Shi, Tao (Frontiers in Neurology, 2023)
Background Multiple cerebral infarcts are usually secondary to cardiogenic embolism, particularly through atrial fibrillation (AF). The three-territory sign (TTS) is an imaging marker that reflects multiple cerebral lesions involving three vascular territories measured by diffusion-weighted imaging (DWI), and the most common etiology is an underlying malignancy. Recent studies have shown that TTS is six times more frequently observed in acute ischemic stroke (AIS) patients with malignancy than in those with AF-related AIS. However, the relevance of TTS to the prognosis of IS patients with malignancy remains unclear. Methods Over a 5-year period (May 2016 to 31 June 2021), AIS admissions with DWI were identified from the First Affiliated Hospital of Xi’an Jiaotong University. Patients were divided into two groups according to whether they had malignancy or AF, resulting in a total of 80 patients with known malignancy (malignancy group) and 92 patients with AF (AF group). All DWI images were reviewed to determine the territory lesion count. Demographic, clinical, and laboratory data, together with radiographic examination data and modified Rankin Scale (mRS) score within a year, were collected. The main outcome was the association between TTS and the prognosis of AIS patients with malignancy, analyzed by a multivariate logistic regression model. Results A total of 172 patients met the selection criteria, including 17 (21.3%) patients in the malignancy group and 8 (8.7%) patients in the AF group with TTS. Age and sex distributions were similar for AIS patients of malignancy and AF. The TTS was 2.4 times more likely to be observed in AIS patients with malignancy compared to AF-related IS patients. The univariate analysis showed that hypertension (OR = 1.137, 95%CI: 1.002–1.291), D-dimer (OR = 1.328, 95%CI: 1.022–1.726), fibrin degradation product (OR = 1.117, 95%CI: 1.010–1.236), and lactate dehydrogenase (LDH; OR = 1.007, 95%CI: 1.000–1.015) were the risk factors for the high mortality rate. Multivariate analysis showed that TTS was the independent risk factor for mortality in AIS patients with malignancy (adjusted OR: 6.866, 95% CI: 1.371–34.395). Conclusion TTS was more frequently observed in AIS patients with malignancy than AF-related AIS and substantially related to high poor outcome (mRS > 2) in AIS patients with malignancy, indicating diagnostic and prognostic value in malignancy-associated hypercoagulation stroke.